Balancing Act - DiLiberto, Lisa (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
This article discusses the challenges of being a professional artist and parent working in the performing arts industry and the measures being taken to create increased accessibility in the sector. It opens with an anecdote by the author recounting moments of exclusion from professional opportunities due to caregiving responsibilities. The article goes on to outline global initiatives created to support artist caregivers in the performing arts and then points to various media responding to this issue. The article introduces the national initiative Balancing Act being developed by Theatre Direct, which aims to support artist caregivers in Canada and concludes with a personal reflection from the author, herself a professional artist, scholar, and mother.